1983
DOI: 10.1161/01.res.52.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Detection of acute myocardial infarction in closed-chest dogs by analysis of regional two-dimensional echocardiographic gray-level distributions.

Abstract: SUMMARY. We hypothesized that acute myocardial infarction could be detected in standard twodimensional echocardiograms of closed-chest dogs by evaluating regional echo amplitude distributions using computerized image analysis. We tested this hypothesis by performing standard, 2.4 MHz two-dimensional echoes before and 2 days after circumflex coronary occlusion in seven closedchest dogs. Control and infarcted regions of interest were studied in digitized stop-frame images. Average gray level was calculated for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…The level at the interface between degenerated myocar-84 Ultrasound in Medicine and Biology Volume 23, Number 1, 1997 dium and fibrosis is calculated as -26.9 dB and is the greatest value among those considered in this study. The clinical echocardiography literature shows that strong echoes are observed at the area of scar in myocardial infarction (Parisi et al 1982;Scorton et al 1983 ) . The dB level of reflected power at the interface between fibrosis and the other tissue elements may be proposed as one of the origin of the strong echo in the myocardial scar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level at the interface between degenerated myocar-84 Ultrasound in Medicine and Biology Volume 23, Number 1, 1997 dium and fibrosis is calculated as -26.9 dB and is the greatest value among those considered in this study. The clinical echocardiography literature shows that strong echoes are observed at the area of scar in myocardial infarction (Parisi et al 1982;Scorton et al 1983 ) . The dB level of reflected power at the interface between fibrosis and the other tissue elements may be proposed as one of the origin of the strong echo in the myocardial scar.…”
Section: Discussionmentioning
confidence: 99%
“…Wall-motion abnormalities, during and after myocardial infarction, can be detected by M-mode echocardiography or by centerline analysis of the two-dimensional echocardiogram (Hikichi and Tanaka 198 la;Moinihan et al 1980;Parisi et al 1980). Ultrasonic tissue characterization of myocardium is also under development (Lattanzi et al 1991(Lattanzi et al , 1992Miller et al 1985;Milunski et al 1989;Mimbs et al 1977;Picano et al 1990Picano et al , 1993Scorton et al 1983). The need to evaluate local myocardial function has increased in proportion to the progress of interven- (Ellis et al 1995;Hannan et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, echocardiographic estimates of stroke volume (SV) have been shown to correlate closely with dye dilution technique measurements. 10 ' u Hence, left ventricular end-diastolic volume (LVEDV) and end-systolic volume (LVESV) were calculated, from which SV was deduced (SV = LVEDV -LVESV). CO (SV x HR) and ejection fraction (SV/LVEDV x 100) were then derived.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…Several studies have pointed out that, despite a normal or supernormal conventional fractional shortening, the midwall left ventricular mechanic is impaired. 3,4 Moreover, a quantitative analysis of the 'texture' of the echocardiographic images, 5,6 represents a useful approach which allows the use of the ultrasound myocardial tissue characterisation (quantitative texture analysis) in this and in other 7 fields of interest. Previously our studies have shown that several myocardial textural videodensitometric parameters are impaired in essential hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%